Case Report: A Virilizing Adrenal Oncocytoma - Kotidis, Efstathios; Bitsianis, Stefanos; Galanos-Demiris, Konstantinos; Christidis, Panagiotis; Mantzoros, Ioannis; Ioannidis, Orestis; Foutsitzis, Vasilis; Pramateftakis, Manousos George; Aggelopoulos, Stamatios (Frontiers in Surgery, 2021)
A 64-year-old female was admitted to our clinic with a 9cm sized adrenal mass. The patient’s main symptom was hirsutism, which included thinning scalp hair and excessive hair growth over her torso and arms. Upon investigation, elevated values of testosterone, androsterone D4, and DHEAS were found. Contrast-enhanced abdominal CT and MRI scans revealed a heterogenous large mass (diameter 9x8,5cm) with focal calcifications, necrotic areas and a clear distinction from the adjacent structures. The patient underwent a right adrenalectomy. The histological examination of the tumor revealed a benign adrenocortical oncocytoma. The patient had an uncomplicated postoperative course and was discharged on postoperative day 8. We also review and provide a summary of the clinical and pathological features of similar cases reported in the literature.